2013
DOI: 10.7314/apjcp.2013.14.5.3191
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antitumor Properties of an Isolate from Leaves of Cassia alata L

Abstract: Leaf extracts of Cassia alata L (akapulko), traditionally used for treatment of a variety of diseases, were evaluated for their potential antitumor properties in vitro. MTT assays were used to examine the cytotoxic effects of crude extracts on five human cancer cell lines, namely MCF-7, derived from a breast carcinoma, SK-BR-3, another breast carcinoma, T24 a bladder carcinoma, Col 2, a colorectal carcinoma, and A549, a nonsmall cell lung adenocarcinoma. Hexane extracts showed remarkable cytotoxicity against M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…alata leaves extracts reveals that the Hexane fraction of C. alata leaves exhibited cytotoxic activity against parental A549 (lung cancer cells) and OV2008 (ovarian cancer cells) cell lines [23], also the hexane fraction and f6l (a mixture of polyunsaturated fatty acid esters) exerted a cytotoxic effect on MCF-7 (breast carcinoma cells), T24 (bladder carcinoma cells) and Col 2 (colorectal carcinoma cells) cell lines in a dose-dependent manner, but were not effective against A549 (non-small cell lung adenocarcinoma) and SK-BR-3 (breast carcinoma cells) cell lines [24]. On the other hand, petroleum ether extract possessed anticancer activity against HCT-15 (colon carcinoma) and Hep2 (Human cervix carcinoma) cell lines [25], while the Chloroform fraction of Cassia alata L showed remarkable cytotoxicity against HepG2 cells [8].…”
Section: Discussionmentioning
confidence: 99%
“…alata leaves extracts reveals that the Hexane fraction of C. alata leaves exhibited cytotoxic activity against parental A549 (lung cancer cells) and OV2008 (ovarian cancer cells) cell lines [23], also the hexane fraction and f6l (a mixture of polyunsaturated fatty acid esters) exerted a cytotoxic effect on MCF-7 (breast carcinoma cells), T24 (bladder carcinoma cells) and Col 2 (colorectal carcinoma cells) cell lines in a dose-dependent manner, but were not effective against A549 (non-small cell lung adenocarcinoma) and SK-BR-3 (breast carcinoma cells) cell lines [24]. On the other hand, petroleum ether extract possessed anticancer activity against HCT-15 (colon carcinoma) and Hep2 (Human cervix carcinoma) cell lines [25], while the Chloroform fraction of Cassia alata L showed remarkable cytotoxicity against HepG2 cells [8].…”
Section: Discussionmentioning
confidence: 99%
“…It has numerous pharmacological activities such as antitumor [10], anthelmintic [11], anti-bacterial [12], anti-oxidant and antiinflammatory [13], and anti-diabetic activities [14]. A recent study found that S. alata (250 and 500 mg/kg) improved abnormal lipid metabolism by suppressing hepatic lipogenic genes, sterol regulatory element binding protein 1c (SREBP1c), fatty acid synthase (FAS) and acetyl-CoA carboxylase (ACC) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, ethanolic extracts of C. sophera proved to be hepatoprotective against carbon tetrachloride induced hepatic damage in rats [13]. In a recent study, the hexane extracts of the Cassia alata showed remarkable cytotoxicity against breast and lung carcinoma cells and the elucidation of hexane extracts revealed the presence of polyunsaturated fatty acids esters [14]. In our study, the chloroform extracts exhibited maximum cytotoxicity against the cell lines in all the plant studied.…”
Section: Discussionmentioning
confidence: 71%